Some mechanisms of psychotherapeutic effects in bibliotherapy - Golzitskaya, Alena A. (2016)
Some mechanisms of bibliotherapy that cause the reader’s personal change are considered in article. Vygotsky’s research in connection with the psychology of art, that became one of the basic in the analysis of functioning of method, are also outlined
Keywords: bibliotheraphy; reader; basic therapeutic mechanisms; book